Mortality Outcomes in People Experiencing Homelessness Across England: a population-based study. (30th September 2020) - Menezes, D; Lewer, D; Yavlinsky, A; Tinelli, M; Aldridge, R
Abstract: Introduction: The number of people experiencing homelessness in England has increased since 2010 and a recent systematic review and meta-analysis demonstrated high levels of mortality in this group across high-income countries. In this study we examine the death rates in people experiencing homelessness after discharge from hospital. Methods: This is a study of linked hospital admission records and mortality data for two groups. First, a "Homeless group": people seen by 17 specialist homeless discharge schemes between 1 November 2013 and 30 November 2016. Second, an "IMD5 group": A matched group of patients who live in deprived areas and have the same age and sex, and were discharged from the same hospital in the same year as the homeless patient. Our analysis entailed calculating mortality rates across each group and by the number of comorbidities. Results: The mortality rate for the IMD5 group was 1, 935 deaths per 100, 000 person years, compared with 5, 691 for the homeless group, giving a rate ratio of 2.9 (95% CI 2.5-3.5). The mortality risk increased with the number of comorbidities. Individuals in the IMD5 group with zero comorbidities had a death rate of 831 per 100, 000 person-years, compared with the homeless group for which the corresponding figure was 2, 598 and or those with 4+ comorbidities were 7, 324 (IMD5) and 12, 714 (homeless). This suggests a 'super-additive' interaction in which the effect of morbidity on mortality risk after discharge is greater for homeless patients. Survival at 5 years for the homelessness group was for men 80% (95% CI 77-85) and women 85 (95% CI 81-87). Conclusions: This study shows that the well-established inequity in mortality for people experiencing homelessness exists after discharge from hospital and is greatest for the most unwell patients. Our results suggest a need for greater emphasis on prevention of homelessness, early healthcare interventions and improved hospital discharge arrangements for this population. Key messages: The well-established inequity in mortality for people experiencing homelessness exists after discharge from hospital and is greatest for the most unwell patients. Our results suggest a need for greater emphasis on prevention of homelessness, early healthcare interventions and improved hospital discharge arrangements for this population.